El principio de actio libera in causa como elemento de imputabilidad en los delitos de tránsito por embriaguez o bajo los efectos de sustancias estupefacientes o psicotrópicas en la forma como esta concebido en la legislación ecuatoriana vulnera el principio de presunción de inocencia - Ordoñez Benavides, Diego René (2015)
One of the phenomena that occur frequently in our social reality is doctrinally known as actio libera in cause, which is essentially the theory that studies the complex events in which the offender subject to the rule is placed in a state of insanity and then commits a crime. The origins of the actio libera in cause are traced back to the middle Ages, and were limited only to cases of voluntary intoxication. So, canonists distinguished between voluntary intoxication which was involuntary, the latter if it was full precluded any degree of responsibility, and if it was incomplete decreased it. However, for the canonists and classic single and drunkenness was punishable. Recall the famous case of Lot, narrated by Genesis; as is known, Lot being drunk maintains sexual intercourse with her daughters, without knowing it, the question then arose was whether, in similar cases, the agent should answer for the act committed in this state, or simply because get drunk. In crimes of commission involving a result, if the agent has committed the act for predictable and controllable effects he intentionally did not want to commit to control the outcome in a state of incapacity or if the agent intentionally gets on disability status by the drug, alcohol or other substances in this state make the outcome, the fact whether the act before the disability status "praecedens actio" is a characteristic unlawful and guilty action poses. The constitutionality of the application of the actio libera in cause as an element of criminal responsibility in traffic offenses committed while intoxicated or under the influence of narcotics or psychotropic substances, violates the principle of presumption of innocence. As the current legislation is designed transit applies an allegedly unconstitutional manner, the legal concept of actio libera in cause to assume that the active criminal traffic offense described subject is always in the ability to predict the consequences of their actions, is presumed under the law of transit drunkenness does not become unforeseeable circumstances or force majeure, but recklessness and negligence of the driver